Leveraging infant visit PrEP screening INtegration & tasK shifting to improve post-partum HIV prevention in Malawi (LINK): a cluster-randomized trial evaluation of a postpartum HIV prevention package among breastfeeding women in Malawi - Sarah E. Rutstein; Valerie A. Lucas; Mina C. Hosseinipour; Michael E. Herce; Jessie Edwards; Caitlin Cassidy; Jimmy Villiera; Funny Kamanga; Maganizo Chagomerana; Joep J. van Oosterhout; Elijah Chikuse; Ethel Rambiki; et al. (BMC Health Services Research)
Abstract Background Elimination of vertical transmission of HIV remains a major global public health priority. In Malawi, more than one-third of pediatric HIV acquisitions are attributed to perinatal HIV acquisition during breastfeeding. HIV pre-exposure prophylaxis (PrEP) is a crucial biomedical tool to keep women free of HIV and eliminate vertical transmission, but effectiveness has been hampered by poor uptake and premature discontinuation. Implementation science approaches are needed to improve uptake, persistence, and adherence to PrEP among postpartum women at risk of HIV. Methods LINK is a type I hybrid effectiveness implementation cluster-randomized trial conducted at 12 service delivery sites within Lilongwe district, Malawi. The LINK model is a novel postpartum HIV prevention package that uses implementation strategies of integration and task-shifting/sharing and includes the following evidence-based practices: (1) maternal HIV testing integrated with Expanded Programme for Immunization (EPI) sites for infant immunizations [integration], (2) PrEP screening and referral for mothers who test HIV-negative, (3) engagement of male partner(s), and (4) community-facility linkage (CFL) peer mother model for PrEP (re)engagement [integration and task shift/share]. Clinics are randomized 1:1 to intervention or control conditions. Effectiveness outcomes include PrEP uptake, adherence, and 6-month persistence among breastfeeding women at intervention compared to control sites. Implementation outcomes assessed at intervention sites include reach, adoption, acceptability, fidelity, scalability, sustainability and cost-effectiveness. We will analyze effectiveness outcomes with routine medical records, surveys, and PrEP drug metabolites via dried blood spots which will provide additional insights into HIV risk and PrEP usage and will facilitate a “constructed cohort” of PrEP eligible postpartum women. Implementation outcomes rely on in-depth interviews, surveys, site assessments, structured observations, and other tools. Human centered design workshops prior to implementation will further inform site-specific procedures for LINK model integration and launch. Discussion The study establishes a simple, scalable model, building on existing HIV and maternal and child health service delivery platforms, to accelerate efforts toward eliminating vertical transmission. If the LINK model is successful at improving PrEP usage among postpartum women, feasible, and cost-effective, we will have the knowledge to support quickly sustaining and scaling the intervention in Malawi and beyond. Trial registration Clinicaltrials.gov NCT06506188 (registered: 2024/07/17).